Associação da apneia obstrutiva do Ssno com bruxismo : um estudo transversal - Blum, Davi Francisco Casa (2016)
Obstructive sleep apnea (OSA) and sleep bruxism (BS) are prevalent diseases and can cause harm to the health of individuals. The association between these diseases has been investigated in recent years and is still inconclusive. The aim of this study was to verify the association of OSA with BS by polysomnography by testing the hypothesis that the BS events index is positively correlated with apnea and hypopnea index (AHI). In this cross-sectional study, 35 patients were diagnosed with OSA (G1) and 10 patients with OSA (GC). Full-night polysomnography was performed in the patients, recording some sleep parameters and rhythmic activity activities of the chewing muscles (RMMA). The evaluated patients (25 men and 20 women) had a mean age of 41 (G1) and 34 (GC) years. It was not (G1 34.4 ± 18.9, GC 5.4 ± 1.5) and RMMA per hour of sleep (G1 21.8 ± 7.2, GC 8.9 ± 10.1), with a positive correlation between these indices (rs 0.613, p <0.001). There is an association between OSA and BS. The rate of RMMA events per hour of sleep is positively correlated with AHI.